Single-machine scheduling with an external resource - Briskorn, Dirk; Davari, Morteza; Matuschke, Jannik (European journal of operational research, 2021)
highlights•We study single-machine scheduling with an external resource.•We look at four different classes of problems with an external resource.•For each class, we consider four different classical objective functions.•We provide a complexity analysis for different members of these four classes. This paper studies the complexity of single-machine scheduling with an external resource, which is rented for a non-interrupted period. Jobs that need this external resource are executed only when the external resource is available. There is a cost associated with the scheduling of jobs and a cost associated with the duration of the renting period of the external resource. We look at four classes of problems with an external resource: a class of problems where the renting period is budgeted and the scheduling cost needs to be minimized, a class of problems where the scheduling cost is budgeted and the renting period needs to be minimized, a class of two-objective problems where both, the renting period and the scheduling cost, are to be minimized, and a class of problems where a linear combination of the scheduling cost and the renting period is minimized. We provide a thorough complexity analysis (NP-hardness proofs and (pseudo-)polynomial algorithms) for different members of these four classes.